Volatile Organic Compounds in Exhaled Air as Novel Marker for Disease Activity in Crohn's Disease: A Metabolomic Approach. Issue 8 (August 2015) - Bodelier, Alexander G. L.; Smolinska, Agnieszka; Baranska, Agnieszka; Dallinga, Jan W.; Mujagic, Zlatan; Vanhees, Kimberly; van den Heuvel, Tim; Masclee, Ad A. M.; Jonkers, Daisy; Pierik, Marie J.; van Schooten, Frederik J.
Abstract : Background: Disappearance of macroscopic mucosal inflammation predicts long-term outcome in Crohn's disease (CD). It can be assessed by ileocolonoscopy, which is, however, an invasive and expensive procedure. Disease activity indices do not correlate well with endoscopic activity and noninvasive markers have a low sensitivity in subgroups of patients. Volatile organic compounds (VOCs) in breath are of increasing interest as noninvasive markers. The aim of this study was to investigate whether VOCs can accurately differentiate between active CD and remission. Methods: Patients participated in a 1-year follow-up study and Harvey–Bradshaw index, blood, fecal, and breath samples were collected at regular intervals. Patients were stratified into 2 groups: active (fecal calprotectin >250 µg/g) or inactive (Harvey–Bradshaw index <4, C-reactive protein <5 mg/L, and fecal calprotectin <100 µg/g) disease. Breath samples were analyzed by gas chromatography–time-of-flight mass spectrometry. Random forest analyses were used to find the most discriminatory VOCs. Results: Eight hundred thirty-five breath-o-grams were measured, 140 samples were assigned as active, 135 as inactive disease, and 110 samples of healthy controls. A set of 10 discriminatory VOCs correctly predicted active CD in 81.5% and remission in 86.4% (sensitivity 0.81, specificity 0.80, AUC 0.80). These VOCs were combined into a single disease activity score that classified disease activity in more than 60% of the previously undetermined individuals. Conclusions: We showed that VOCs can separate healthy controls and patients with active CD and CD in remission in a real-life cohort. Analysis of exhaled air is an interesting new noninvasive application for monitoring mucosal inflammation in inflammatory bowel disease. Abstract : Article first published online 8 May 2015Supplemental Digital Content is Available in the Text.